Giant rhinophyma in a bronchial asthma patient treated by excision and full thickness skin grafting - Köse, Rüstü; Okur, M. Ihsan; Güldür, M. Emin (My University, 2008)
A 72-year-old man presented with an unusually severe case of rhinophyma. The pedunculated mass was widely excised and a skin graft from the medial upper arm was applied. A very satisfactory cosmetic result was obtained. © 2008 Dermatology Online Journal.
Keywords: Aged; Asthma; Fibrosis; Humans; Hyperplasia; Male; Nasal Obstruction; Nose Deformities, Acquired; Rhinophyma; Rhinoplasty; Sebaceous Glands; Skin Transplantation; Social Isolation; salmeterol xinafoate; tiotropium bromide; acanthosis; aged; article; asthma; cancer surgery; case report; cauterization; clinical examination; full thickness skin graft; hemostasis; histopathology; human; human tissue; male; nose cartilage; nose obstruction; perichondrium; rosacea; sebaceous gland; skin fibrosis; tumor growth; asthma; fibrosis; hyperplasia; nose injury; nose obstruction; nose reconstruction; pathology; psychological aspect; rosacea; skin transplantation; social isolation